VISIBILITY AND POSTURE OF OPERATORS IN HARVESTERS WITH LATERAL AND FRONT COUPLING CRANES - Oliveira, Felipe Martins de; Lopes, Eduardo da Silva; Fiedler, Nilton Cesar; Martins, Alysson Braun (Floresta, 2023)
In mechanized timber harvesting operations, it is possible to verify ergonomic inadequacies, such as poor visibility and inappropriate postures, which can cause risks to the safety and health of workers, with effects on the operational performance of the machines. In this context, the objective of this work was to evaluate the effects of the positioning of the coupling crane in harvesters concerning the visibility and postures of forestry operators. For this, the study was carried out in clear-cutting operations in eucalyptus stands, evaluating a harvester with a frontal coupling crane and another with lateral coupling, as well as operators per machine. To determine effective times and typical postures, filming and freezing of images were performed. Then, the Skogforsk and Rapid Upper-Limb Assessment (RULA) methods were used to assess visibility and posture, respectively. Angulation and posture data were compared between machines by the Student’s t test. Front and side visibility remained within acceptable limits, but the side crane harvester required operators to have an average head tilt angle of 15º, 50% higher than with the front crane. Consequently, in the postural evaluation, the one with the lateral crane presented score 3 and action level 2 86% of the time, suggesting further investigations, while the other presented score 2 and action level 1 81% of the time, being acceptable if not maintained or repeated for long periods. Therefore, the positioning of the crane coupling on the machine requires a reorganization of the workstation, mainly the machine’s display.